2021
DOI: 10.31857/s020736760015992-0
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the theoretical background of the cluster concept

Abstract: This article explores the concepts of the theory of cluster development, which are multifaceted and differ from each other in their heterogeneity, both in Russia and abroad. It has been determined that cluster formations are based on cooperative ties, and characterized by fair competition, which implies the supply of raw materials, the production process, and the market for goods and services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Yaroshenko et al. (2004) reported that the addition of 0.4 and 0.8 ppm of selenium caused a significant decrease in the amount of malonaldehyde in thigh and breast meat. These researchers reported that with increasing dietary selenium, the concentration of glutathione peroxidase enzyme in plasma and cell membrane increased.…”
Section: Discussionmentioning
confidence: 99%
“…Yaroshenko et al. (2004) reported that the addition of 0.4 and 0.8 ppm of selenium caused a significant decrease in the amount of malonaldehyde in thigh and breast meat. These researchers reported that with increasing dietary selenium, the concentration of glutathione peroxidase enzyme in plasma and cell membrane increased.…”
Section: Discussionmentioning
confidence: 99%